Ischemia Enhances the Acute Stretch-Induced Increase in Calcium Spark Rate in Ventricular Myocytes - Cameron, Breanne A.; Kai, Hiroaki; Kaihara, Keiko; Iribe, Gentaro; Quinn, T. Alexander (Frontiers in Physiology, 2020)
Introduction: In ventricular myocytes, spontaneous release of calcium (Ca2+) from the sarcoplasmic reticulum via ryanodine receptors (‘Ca2+ sparks’) is acutely increased by stretch, due to a stretch-induced increase of reactive oxygen species (ROS). In acute regional ischemia there is stretch of ischemic tissue, along with an increase in Ca2+ spark rate and ROS production, each of which has been implicated in arrhythmogenesis. Yet, whether there is an impact of ischemia on the stretch-induced increase in Ca2+ sparks and ROS has not been investigated. We hypothesized that ischemia would enhance the increase of Ca2+ sparks and ROS that occurs with stretch. Methods: Isolated ventricular myocytes from mice (male, C57BL/6J) were loaded with fluorescent dye to detect Ca2+ sparks (4.6 µM Fluo-4, 10 min) or ROS (1 µM DCF, 20 min), exposed to normal Tyrode (NT) or simulated ischemia (SI) solution (hyperkalemia [15 mM potassium], acidosis [6.5 pH], and metabolic inhibition [1 mM sodium cyanide, 20 mM 2-deoxyglucose]), and subjected to sustained stretch by the carbon fiber technique ( 10% increase in sarcomere length, 15 s). Ca2+ spark rate and rate of ROS production were measured by confocal microscopy. Results: Baseline Ca2+ spark rate was greater in SI (2.54+/-0.11 sparks·s-1·100 um-2; n=103 cells, N=10 mice) than NT (0.29+/-0.05 sparks·s-1·100 um-2; n=33 cells, N=9 mice; p<0.0001). Stretch resulted in an acute increase in Ca2+ spark rate in both SI (3.03+/-0.13 sparks·s-1·100 um-2; p<0.0001) and NT (0.49+/-0.07 sparks·s-1·100 um-2; p<0.0001), with the increase in SI being greater than NT (+0.49+/-0.04 vs +0.20+/-0.04 sparks·s-1·100 um-2; p<0.001). Similarly, baseline rate of ROS production was greater in SI (1.01+/-0.01 normalized slope; n=11, N=8 mice) than NT (0.98+/-0.01 normalized slope; n=12, N=4 mice; p<0.05), but there was an acute increase with stretch only in SI (+12.5+/-2.6%; p<0.001). Conclusion: Ischemia enhances the stretch-induced increase of Ca2+ sparks in ventricular myocytes, with an associated enhancement of stretch-induced ROS production. This effect may be important for premature excitation and/or in the development of an arrhythmogenic substrate in acute regional ischemia.